A ceramic oxide hydrogen permeation-blocking composite coating and a preparation method thereof

A ceramic oxide composite coating with mixed oxides and an inorganic adhesive addresses the limitations of existing coatings by offering superior hydrogen barrier, thermal shock resistance, and lead-bismuth corrosion resistance, suitable for high-pressure and high-temperature environments in complex components.

CN116851238BActive Publication Date: 2024-12-27GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310792689.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-27
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

Current hydrogen barrier coatings face issues such as oxidation at high temperatures, cracking, poor bonding with substrates, and high costs, making them unsuitable for high-pressure and high-temperature environments, especially in complex structural components like small-diameter long pipes.

Method used

A ceramic oxide hydrogen permeation barrier composite coating composed of mixed oxides (α-Al2O3, CaO, Cr2O3, and glass powder) with an inorganic adhesive, applied via a slurry method, providing excellent hydrogen barrier performance, thermal shock resistance, and bonding strength, and resistance to lead-bismuth corrosion.

Benefits of technology

The coating exhibits high hydrogen barrier performance, stable resistance to thermal shocks, and resistance to lead-bismuth corrosion, with a controllable thickness and low cost, suitable for mass production and application in complex structural components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116851238B_ABST
    Figure CN116851238B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of hydrogen barrier coatings, and in particular to a ceramic oxide hydrogen barrier composite coating and a preparation method thereof, comprising the following raw materials by mass fraction: 12-16% of mixed oxide, 55-57% of inorganic adhesive and 28-32% of water, wherein the mixed oxide comprises the following raw materials by mass fraction: α-Al 2 O 3 15‑20%, CaO 10‑15%, Cr 2 O 3 5‑10% and glass powder 45‑60%. The ceramic oxide hydrogen permeation barrier composite coating of the present invention has stable hydrogen barrier performance, and the hydrogen permeation factor (PRF) can reach 46340 at a pressure of 75 kPa and a temperature of 650°C. In addition, the coating has good resistance to lead-bismuth corrosion and thermal shock, and its preparation process is simple, the preparation cycle is short, the thickness is controllable, the cost is low, and it can meet the needs of mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen barrier coatings, and in particular to a ceramic oxide hydrogen penetration barrier composite coating and a preparation method thereof. Background Art

[0002] As a renewable and clean energy, hydrogen energy has extremely wide applications in transportation, electricity, and industry. The extraction, storage, and transportation of hydrogen energy play a vital role in the further development of the hydrogen energy industry in the future. At the same time, the penetration and diffusion of hydrogen in the matrix material is a serious problem currently facing the hydrogen energy industry. These problems will cause the plasticity of the matrix material to decrease, the fatigue crack growth rate to accelerate, and eventually lead to material failure, posing a great threat to production and environmental safety. Therefore, the development of new hydrogen barrier coating technology is an effective way to solve the hydrogen penetration problem and meet the development needs of the hydrogen energy and nuclear energy industries.

[0003] In order to reduce the damage caused by hydrogen penetration, hydrogen permeation barrier coatings are used as permeation barriers to prevent hydrogen and its isotopes from penetrating and diffusing into the matrix material. At the same time, it ensures that the coating is suitable for high temperature, high pressure and strong radiation service environments, and meets the coating requirements of different complex structural components. Domestic and foreign scholars have carried out research on hydrogen permeation barrier coating technology.

[0004] At present, through extensive research and screening of various coatings such as oxides, silicides, titanium-based ceramics, and comprehensive consideration of hydrogen permeation resistance, material compatibility, radiation stability, and the requirements of liquid metal thin layers for coating insulation, the types of coating materials have developed from diversification to the current main types of oxides such as Al2O3, Cr2O3, Er2O3, Y2O3 and their composite coatings.

[0005] However, there are still many problems with hydrogen barrier coatings in the prior art. For example, titanium-based coatings are prone to oxidation at 450°C and cannot be used in high temperature and high pressure environments; silicon-based coatings are prone to falling off and cracking when the thickness increases. The commonly used coating preparation methods currently include vapor deposition, magnetron sputtering, embedded aluminization, sol-gel, etc. Among them, the aluminum oxide coatings prepared by magnetron sputtering and embedded aluminization cannot meet the requirements of pipeline inner wall coating, and are expensive and cannot be prepared in large quantities; the coatings prepared by the sol-gel method have poor bonding with the substrate, are easy to fall off, the coating is relatively loose, there are holes on the surface, the hydrogen barrier performance is poor, and the thickness is difficult to control.

[0006] In view of this, the present invention proposes a high-temperature resistant ceramic oxide hydrogen penetration barrier composite coating that can be applied to the surface of substrates such as 316L stainless steel and carbon steel. The coating has excellent hydrogen barrier properties, good thermal shock resistance and bonding strength, and certain resistance to lead-bismuth corrosion. Summary of the invention

[0007] The purpose of the present invention is to provide a ceramic oxide hydrogen permeation barrier composite coating and a preparation method thereof, wherein the coating has excellent hydrogen barrier performance, good thermal shock resistance and bonding strength, and has certain lead-bismuth corrosion resistance.

[0008] In a first aspect, the present invention provides a ceramic oxide hydrogen permeation barrier composite coating, comprising the following raw materials in mass fractions:

[0009] Mixed oxide 12-16%, inorganic adhesive 55-57% and water 28-32%,

[0010] The mixed oxide comprises the following raw materials in mass fractions: α-Al2O3 15-20%, CaO 10-15%, Cr2O3 5-10% and glass powder 45-60%.

[0011] In the ceramic oxide hydrogen permeation barrier composite coating of the present invention, α-Al2O3 has the advantages of good hydrogen permeation barrier performance, high temperature stability, good compatibility with liquid lithium lead, etc.; chromium oxide can reduce the thermal mismatch between the coating and the substrate, has good compatibility, and has good high temperature oxidation resistance and wear resistance; glass powder can reduce the melting point of the coating, make the powder easy to sinter, play the role of welding oxide powder, and it has a large thermal expansion coefficient, which is conducive to the combination of the coating and the substrate. At the same time, the glass powder melts at high temperature to reduce the porosity of the coating and increase the density, thereby forming a dense glassy adhesion layer on the surface of the substrate; calcium oxide can reduce the viscosity and surface tension of the coating at high temperature with sodium oxide and potassium oxide contained in the inorganic silicone adhesive, so that the coating is not prone to bubbles, polycondensation and shedding. Finally, the above-mentioned mixed oxide is mixed with the inorganic silicone adhesive, and solidified, sintered and welded at high temperature to further increase the hardness of the coating and improve the corrosion resistance and high temperature resistance of the coating. The coating has excellent hydrogen barrier properties, good thermal shock resistance and bonding strength, and has certain resistance to lead-bismuth corrosion. It can be used as a hydrogen penetration barrier for complex structural components, especially for the inner wall of small-diameter long pipes.

[0012] As a preferred embodiment of the present technical solution, the glass powder used in the present invention is preferably lead-free glass powder with a melting point of 800-900° C., and the inorganic adhesive is preferably a high-temperature resistant inorganic silicone adhesive.

[0013] The main components of high-temperature resistant inorganic silicone adhesives are silicon micropowder, sodium silicate, potassium silicate, etc. The calcium oxide in the mixed oxide powder and the sodium oxide and potassium oxide contained in the inorganic silicone adhesive can reduce the viscosity and surface tension of the coating at high temperatures, making the coating less likely to have bubbles, condensation and falling off.

[0014] As a preferred embodiment of the present technical solution, the ceramic oxide hydrogen penetration barrier composite coating is formed by curing, sintering and welding a mixed oxide powder and an inorganic silicone adhesive at a high temperature.

[0015] During the high-temperature curing and sintering process, the mixed oxide powder interacts with the inorganic silicone adhesive. The adhesive melts at high temperature, and the surface liquid phase fills the pores inside the coating, which can better weld the evenly dispersed oxide particles, fill the gaps between the powder particles, and promote the densification process of the coating.

[0016] In a second aspect, the present invention also provides a method for preparing the above ceramic oxide hydrogen permeation barrier composite coating, comprising the following steps:

[0017] S1. Evenly mix the mixed oxide and the inorganic adhesive to prepare a coating;

[0018] S2, spraying the coating onto the surface of the base material;

[0019] S3. Place the sprayed substrate in the atmosphere or oxygen-rich atmosphere, heat it to 400-500°C at a rate of 3-8°C, keep it warm for 20-40 minutes, continue to heat it to 800-900°C, keep it warm for 20-40 minutes, cool it to room temperature with the furnace, and obtain a ceramic oxide hydrogen penetration barrier composite coating on the surface of the substrate.

[0020] The ceramic oxide hydrogen permeation barrier composite coating of the present invention has simple preparation process, short preparation cycle, controllable thickness and low cost, and can meet the needs of mass production.

[0021] As a preferred embodiment of the present technical solution, in step S1, the mixed oxide is first ball-milled, and then the mixed oxide powder after ball-milling is mixed with an inorganic adhesive, and deionized water is added to adjust the viscosity, and the mixture is ultrasonically mixed and sieved so that the coating can obtain a dense coating on the surface of the substrate.

[0022] As a preferred embodiment of the present technical solution, during the ball milling, mixed oxides are added to the planetary ball mill, and a small amount of anhydrous ethanol is added to further improve the ball milling effect. During the ball milling process, the ball-to-material ratio is controlled to be 2:1, and the ball milling time is 10-14h.

[0023] As a preferred embodiment of the present technical solution, during the ultrasonic mixing, the ultrasonic frequency is 30-50KHz, and preferably 40KHz for 10-30min.

[0024] As a preferred embodiment of the present technical solution, in step S2, during spraying, the air inlet pressure of the spray gun is preferably 2-3.5 bar, and the number of spraying times is preferably 2-4 times.

[0025] The use of spraying equipment to atomize the slurry can not only achieve uniform coating on the inner wall of small pipes (minimum diameter 5mm) and the surface of block substrates, but also adjust the coating thickness by the number of spraying times and the air pressure of the spray gun.

[0026] As a preferred embodiment of the present technical solution, the material of the substrate includes any one of stainless steel and carbon steel; and the substrate can exist in the form of any one of a planar device, a metal wire tube and a special-shaped device.

[0027] As a preferred embodiment of the present technical solution, before spraying, the substrate sample is cut by electric spark cutting, the surface to be sprayed is roughened with sandpaper, and ultrasonic cleaning is performed in ethanol for 10-20 minutes to remove rust and dirt from the surface of the substrate material and roughen it, wherein during the roughening, 240# and 400# metallographic sandpapers are used in sequence for polishing.

[0028] The ceramic oxide hydrogen permeation barrier composite coating of the present invention has at least the following technical effects:

[0029] 1. In the ceramic oxide hydrogen permeation barrier composite coating of the present invention, α-Al2O3 has the advantages of good hydrogen permeation barrier performance, high temperature stability, and good compatibility with liquid lithium lead; chromium oxide can reduce the thermal mismatch between the coating and the substrate, has good compatibility, and has good high temperature oxidation resistance and wear resistance; and glass powder can reduce the melting point of the coating, so that the powder is easy to sinter, and plays the role of welding oxide powder, and it has a large thermal expansion coefficient, which is conducive to the combination of the coating and the substrate. At the same time, the melting of glass powder at high temperature can reduce the porosity of the coating and increase the density, thereby forming a dense glassy adhesion layer on the surface of the substrate; calcium oxide can reduce the viscosity and surface tension of the coating at high temperature with sodium oxide and potassium oxide contained in the inorganic silicone adhesive, so that the coating is not prone to bubbles, condensation and shedding. Finally, the above-mentioned mixed oxide is mixed with the inorganic silicone adhesive, and the hardness of the coating is increased by the inorganic silicone adhesive, thereby improving the corrosion resistance and high temperature resistance of the coating;

[0030] 2. The ceramic oxide hydrogen permeation barrier composite coating of the present invention adopts a slurry method as the coating preparation method, which has simple equipment requirements, can be prepared in large quantities, has a short preparation cycle, and can be evenly coated on the inner wall of a small pipe (minimum diameter 5mm) and the surface of a block substrate by atomizing the slurry through a spraying device. The coating thickness can also be adjusted by the number of spraying times and the spray gun air pressure;

[0031] 3. The ceramic oxide hydrogen permeation resistance composite coating of the present invention has stable hydrogen resistance performance. At a pressure of 75 kPa and a temperature of 650°C, the hydrogen permeation resistance factor (PRF) can reach 46340;

[0032] 4. The ceramic oxide hydrogen permeation barrier composite coating of the present invention can be used as a hydrogen permeation barrier layer for complex structural components, especially for the inner wall of a small-diameter long pipeline. Its thermal expansion coefficient has a good match with a substrate such as 316L stainless steel and carbon steel, and thus has a good bonding force with the substrate and is not easy to fall off. The inner wall of the pipeline and the surface of the block substrate are smooth and dense, without falling off and cracking, and there are no voids, microcracks and bubbles under high-power electron microscope observation;

[0033] 5. The ceramic oxide hydrogen permeation barrier composite coating of the present invention has certain resistance to lead-bismuth corrosion. When kept in liquid lead-bismuth at 650°C for 100 hours, the lead-bismuth penetration depth of the substrate without coating protection is about 9.54 μm, while the substrate under coating protection is not affected by lead-bismuth corrosion, and the coating is stable in the lead-bismuth corrosion solution without falling off;

[0034] 6. The ceramic oxide hydrogen permeation barrier composite coating of the present invention has good thermal shock resistance. The coating does not fall off or crack after ten thermal shock cycles.

[0035] 7. The ceramic oxide hydrogen permeation barrier composite coating of the present invention has a simple preparation process, a short preparation cycle, controllable thickness, and low cost, and can meet the needs of mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a cross-sectional view of the coating prepared by the present invention on the inner wall of a pipe;

[0038] Figure 2 The figure is a physical picture of the inner wall coating of pipelines with different diameters according to the present invention;

[0039] Figure 3 is the hydrogen permeation resistance factor of the coating of the present invention;

[0040] Figure 4 This is a physical picture of the coated wafer of the present invention;

[0041] Figure 5 The SEM microstructure diagram of the coating surface of the present invention;

[0042] Figure 6 is the bonding strength between the coating of the present invention and the 316L stainless steel substrate;

[0043] Figure 7The SEM images of the surface of the coating of the present invention after different thermal shock times;

[0044] Figure 8 The anti-lead-bismuth corrosion results of the uncoated substrate of the present invention;

[0045] Fig. 9 The results of the lead-bismuth corrosion resistance of the substrate and the hydrogen permeation-blocking composite coating of the present invention are as follows;

[0046] Fig.10 This is a SEM image of the coating obtained in Comparative Example 1 of the present invention;

[0047] Fig.11 is the hydrogen permeation resistance factor of the coating obtained in Comparative Example 2 of the present invention;

[0048] Fig.12 It is the hydrogen permeation resistance factor of the coating obtained in Control Example 3 of the present invention. DETAILED DESCRIPTION

[0049] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0050] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0051] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Example 1

[0053] Matrix material pretreatment

[0054] The inner wall of 316L stainless steel pipes with different diameters (5 mm and 20 mm) was used as the base material, and the surface of the base material was derusted, decontaminated and roughened before coating;

[0055] During the roughening process, 240# and 400# sandpaper were used to cross-grind the inner wall of the pipe along the axial and radial directions, and then cleaned with clean water;

[0056] The cleaned substrate material is placed in an ethanol solution, and the surface oil stains and residual impurities are cleaned ultrasonically;

[0057] After ultrasonic cleaning for 10 minutes, put it in a drying oven and dry it for 10 minutes before taking it out.

[0058] Preparation of Ceramic Oxide Composite Coatings to Block Hydrogen Penetration

[0059] S1. Prepare 100g of mixed oxide powder in a mass ratio of α-Al2O3: glass powder: CaO: Cr2O3 = 4:12:3:2, then transfer the prepared powder into the tank of a planetary ball mill, pour in a small amount of anhydrous ethanol, with a ball-to-material ratio of 2:1, ball mill for 12h, take out the milled powder, and sieve it with a 200-mesh sieve;

[0060] Prepare the coating in the mass ratio of mixed oxide powder: inorganic silicone adhesive: deionized water = 1:4:2, and ultrasonically disperse the prepared coating for 20 minutes. Stir the coating during the ultrasonic process to make the coating uniform, and sieve the coating through a 200-mesh sieve for storage;

[0061] S2. Take out the pre-treated 316L stainless steel pipe substrate, transfer the coating to the feed tank in the pipe inner wall spraying equipment, adjust the spray gun air inlet pressure to 2.5 bar, move the spray gun rod backward from the pipe mouth at a speed of 1 cm / s, repeat the spraying once, and then place the coated pipe in a 60°C drying oven for 2 hours of drying;

[0062] S3. The dried pipe is transferred to a muffle furnace and further sintered and solidified in air or oxygen-rich atmosphere. The temperature is raised to 450°C at a heating rate of 5°C / min and kept for 30 minutes. The temperature is further raised to 850°C and kept for 30 minutes. After cooling to room temperature in the furnace, the pipe is taken out to obtain a ceramic oxide hydrogen penetration barrier composite coating on the surface of the substrate.

[0063] Example 2

[0064] Matrix material pretreatment

[0065] A 316L stainless steel disc with a diameter of 12 mm and a thickness of 1.2 mm was used as the base material, and the surface of the base material was derusted, decontaminated and roughened before coating;

[0066] During the roughening process, 240# and 400# sandpaper were used to cross-grind the inner wall of the pipe along the axial and radial directions, and then cleaned with clean water;

[0067] The cleaned substrate material is placed in an ethanol solution, and the surface oil stains and residual impurities are cleaned ultrasonically;

[0068] After ultrasonic cleaning for 10 minutes, put it in a drying oven and dry it for 10 minutes before taking it out.

[0069] Preparation of Ceramic Oxide Composite Coatings to Block Hydrogen Penetration

[0070] S1. Prepare 100g of mixed oxide powder in a mass ratio of α-Al2O3: glass powder: CaO: Cr2O3 = 4:12:3:2, then transfer the prepared powder into the tank of a planetary ball mill, pour in a small amount of anhydrous ethanol, with a ball-to-material ratio of 2:1, ball mill for 12h, take out the milled powder, and sieve it with a 200-mesh sieve;

[0071] Prepare the coating in the mass ratio of mixed oxide powder: inorganic silicone adhesive: deionized water = 1:4:2, and ultrasonically disperse the prepared coating for 20 minutes. Stir the coating during the ultrasonic process to make the coating uniform, and sieve the coating through a 200-mesh sieve for storage;

[0072] S2. Take out the pre-treated 316L stainless steel tube disc, drip the coating on the surface of the disc through a dropper, adjust the tilt angle and rotate the disc, evenly apply the coating with a certain fluidity on the surface, and let the excess coating flow out along the edge of the disc. During the process, the disc is continuously rotated in the same direction to ensure that the coating is sufficiently uniform on the surface; when the coating surface is slightly dry and cannot flow, place the coated disc in a 60°C drying oven for 2 hours for drying;

[0073] S3. The dried pipe is transferred to a muffle furnace and further sintered and solidified in air or oxygen-rich atmosphere. The temperature is raised to 450°C at a heating rate of 5°C / min and kept for 30 minutes. The temperature is further raised to 850°C and kept for 30 minutes. After cooling to room temperature in the furnace, the pipe is taken out to obtain a ceramic oxide hydrogen penetration barrier composite coating on the surface of the substrate.

[0074] Example 3

[0075] Matrix material pretreatment

[0076] The inner wall of a carbon steel pipe with a diameter of 10 mm is used as the base material, and the surface of the base material is derusted, decontaminated and roughened before coating;

[0077] During the roughening process, 240# and 400# sandpaper were used to cross-grind the inner wall of the pipe along the axial and radial directions, and then cleaned with clean water;

[0078] The cleaned substrate material is placed in an ethanol solution, and the surface oil stains and residual impurities are cleaned ultrasonically;

[0079] After ultrasonic cleaning for 10 minutes, put it in a drying oven and dry it for 10 minutes before taking it out.

[0080] Preparation of Ceramic Oxide Composite Coatings to Block Hydrogen Penetration

[0081] S1. Prepare 100g of mixed oxide powder in a mass ratio of α-Al2O3: glass powder: CaO: Cr2O3 = 4:12:3:2, then transfer the prepared powder into the tank of a planetary ball mill, pour in a small amount of anhydrous ethanol, with a ball-to-material ratio of 2:1, ball mill for 12h, take out the milled powder, and sieve it with a 200-mesh sieve;

[0082] Prepare the coating in the mass ratio of mixed oxide powder: inorganic silicone adhesive: deionized water = 1:4:2, and ultrasonically disperse the prepared coating for 20 minutes. Stir the coating during the ultrasonic process to make the coating uniform, and sieve the coating through a 200-mesh sieve for storage;

[0083] S2. Take out the pretreated carbon steel pipe substrate, transfer the coating to the feed tank in the pipe inner wall spraying equipment, adjust the spray gun air inlet pressure to 3 bar, move the spray gun rod backward from the pipe mouth at a speed of 1 cm / s, repeat the spraying twice, and place the coated pipe in a 60°C drying oven for 2 hours of drying;

[0084] S3. The dried pipe is transferred to a muffle furnace and further sintered and solidified in air or oxygen-rich atmosphere. The temperature is raised to 400°C at a heating rate of 5°C / min and kept at this temperature for 40 minutes. The temperature is then raised to 900°C and kept at this temperature for 20 minutes. The pipe is taken out after cooling to room temperature in the furnace to obtain a ceramic oxide hydrogen penetration barrier composite coating on the surface of the substrate.

[0085] Example 4

[0086] The composition of the mixed oxide powder is: α-Al2O3: glass powder: CaO: Cr2O3 = 3:9:2:1;

[0087] The composition of the coating is: mixed oxide powder: inorganic silicone adhesive: deionized water = 12:55:28;

[0088] The other preparation processes are basically the same as those in Example 2.

[0089] Example 5

[0090] The composition of the mixed oxide powder is: α-Al2O3: glass powder: CaO: Cr2O3 = 3:10:3:2;

[0091] The composition of the coating is: mixed oxide powder: inorganic silicone adhesive: deionized water = 16:57:32;

[0092] The other preparation processes are basically the same as those in Example 2.

[0093] Example 6

[0094] The composition of the mixed oxide powder is: α-Al2O3: glass powder: CaO: Cr2O3 = 4:10:2:2;

[0095] The composition of the coating is: mixed oxide powder: inorganic silicone adhesive: deionized water = 14:55:30;

[0096] The other preparation processes are basically the same as those in Example 2.

[0097] Comparative Example 1

[0098] α-Al2O3, CaO, Cr2O3 and inorganic silica adhesive are used, water is used as solvent, and no glass powder is added, wherein in the mixed oxide powder, α-Al2O3: glass powder: CaO: Cr2O3 = 4:3:2, and the mixed oxide powder: inorganic adhesive = 1:4;

[0099] The other preparation processes are basically the same as those in Example 2.

[0100] The surface morphology of the coating was observed using a scanning electron microscope. Fig.10 It can be seen that the coating prepared in this comparative example has a very low density and contains many hole defects and oxide particles.

[0101] Comparative Example 2

[0102] Use α-Al2O3, CaO, Cr2O3, glass powder, inorganic silicone adhesive, and water as solvent, wherein in the mixed oxide powder, α-Al2O3: glass powder: CaO: Cr2O3 = 4:12:3:2, increase the proportion of the mixed oxide powder in the coating, and the mixed oxide powder: inorganic adhesive = 3:7;

[0103] The other preparation processes are basically the same as those in Example 2.

[0104] The results of hydrogen barrier test show that at 75kPa and 650℃, the hydrogen barrier factor of the coating is about 36860 ( Fig.11 ).

[0105] Comparative Example 3

[0106] Use α-Al2O3, CaO, Cr2O3, glass powder, inorganic silicone adhesive, and water as solvent, wherein in the mixed oxide powder, α-Al2O3: glass powder: CaO: Cr2O3 = 4:12:3:2, increase the proportion of the mixed oxide powder in the coating, and the mixed oxide powder: inorganic adhesive = 2:3;

[0107] The other preparation processes are basically the same as those in Example 2.

[0108] The results of hydrogen barrier test show that at 75 kPa and 650 °C, the hydrogen barrier factor of the coating is reduced to about 866 ( Fig.12 ).

[0109] The hydrogen barrier factor of the prepared coating was calculated by testing the deuterium ion current density of the substrate at a pressure of 75 kPa and a temperature of 650° C. Table 1 shows the test results of the hydrogen barrier factor of the coatings prepared in Examples 1-6 and Comparative Examples 1-3.

[0110] Table 1 Hydrogen barrier factors of the coatings obtained in Examples 1-6 and Comparative Examples 1-3 (test conditions: 75 kPa, 650°C)

[0111] Serial number Hydrogen barrier factor Example 1 — Example 2 46340 Example 3 — Example 4 42130 Example 5 39650 Example 6 41280 Comparative Example 1 — Comparative Example 2 36860 Comparative Example 3 866

[0112] It can be seen from Table 1 that the hydrogen barrier factor of the coatings obtained in Examples 1-6 of the present invention can reach 46340, indicating that the coatings prepared by this method have excellent hydrogen barrier properties.

[0113] The coating prepared in Control Example 1 has a very low density and contains many hole defects and oxide particles. This may be because the lack of glass powder results in poor bonding between the coating and the substrate, and also results in a high melting point of the coating, making it impossible to form a dense glassy adhesion layer on the substrate surface.

[0114] Comparative Examples 2-3 increase the content of mixed oxides with hydrogen permeation resistance, but the hydrogen resistance of the prepared coating is much lower than that of Examples 1-6. This may be because when the proportion of oxides increases further, the inorganic silica adhesive is not enough to weld the oxide particles, and the interconnected pores and bubbles generated inside gradually increase, which affects the density of the coating, resulting in an increase in the channels for hydrogen to enter the substrate. It is further explained that the excellent technical effect of the coating of the present invention is the result of the interaction of the components in the coating, not that the higher the content of mixed oxides with good hydrogen resistance, the better.

[0115] In addition, by Figure 1 It can be seen that the thickness of the coating obtained in Example 1 of the present invention is about 35-70 μm, and the coating thickness is evenly distributed.

[0116] Figure 2 This is a real picture of the inner wall coating of pipes with different diameters. Figure 3 The actual picture of the coated disc shows that the surface of the coating prepared by the present invention is smooth and flat. Figure 5 It can be seen from the SEM image that the coating is sufficiently flat and has no cracks.

[0117] The present invention also uses the acoustic emission method to test the bonding strength between the coating of Example 1 and the 316L stainless steel substrate, which is about 66N. It can be seen that the coating has good bonding strength and is not easy to fall off ( Figure 6 ); Moreover, the coating also has good thermal shock resistance. After ten thermal shock cycles, the coating did not fall off or crack ( Figure 7 ).

[0118] The present invention further heats the uncoated substrate and the coating in liquid lead-bismuth at 650°C for 100 hours to study the coating's resistance to lead-bismuth corrosion. Figure 8-9 It can be seen that the lead-bismuth penetration depth of the substrate without coating protection is about 9.54μm, while the substrate under coating protection is not affected by lead-bismuth corrosion, and the coating is stable in the lead-bismuth corrosion solution and does not fall off, indicating that the coating has excellent resistance to lead-bismuth corrosion.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ceramic oxide hydrogen permeation barrier composite coating, characterized in that: It is composed of the following raw materials by mass fraction: Mixed oxide 12-16%, inorganic adhesive 55-57% and water 28-32%, The mixed oxide is composed of the following raw materials in mass fractions: α-Al2O3 15-20%, CaO 10-15%, Cr2O3 5-10% and glass powder 45-60%; The glass powder is lead-free glass powder with a melting point of 800-900° C., and the inorganic adhesive is a high-temperature resistant inorganic silicone adhesive, the components of which include silicon micropowder, sodium silicate and potassium silicate; The ceramic oxide hydrogen permeation barrier composite coating is formed by curing, sintering and welding a mixed oxide powder and an inorganic silica adhesive at a high temperature. The method for preparing the ceramic oxide hydrogen permeation-blocking composite coating comprises the following steps: S1. Evenly mix the mixed oxide and the inorganic adhesive to prepare a coating; S2, spraying the coating onto the surface of the base material; S3, placing the sprayed substrate in the atmosphere or oxygen-rich atmosphere, heating it to 400-500°C at a rate of 3-8°C, keeping it warm for 20-40 minutes, and then heating it to 800-900°C, keeping it warm for 20-40 minutes, and cooling it to room temperature with the furnace to obtain a ceramic oxide hydrogen penetration barrier composite coating on the surface of the substrate; The material of the substrate is any one of stainless steel and carbon steel.

2. The ceramic oxide hydrogen permeation barrier composite coating according to claim 1, characterized in that: In step S1, the mixed oxide is firstly ball-milled, and then the mixed oxide powder after ball-milling is mixed with an inorganic adhesive, and deionized water is added to adjust the viscosity, and ultrasonic mixing is performed to obtain a coating.

3. The ceramic oxide hydrogen permeation barrier composite coating according to claim 2, characterized in that: During the ball milling, the mixed oxides and anhydrous ethanol are added to the planetary ball mill, the ball-to-material ratio is controlled to be 2:1, and the ball milling is performed for 10-14 hours.

4. The ceramic oxide hydrogen permeation barrier composite coating according to claim 2, characterized in that: During the ultrasonic mixing, the ultrasonic frequency is controlled to be 30-50 KHz and the time is 10-30 min.

5. The ceramic oxide hydrogen permeation barrier composite coating according to claim 1, characterized in that: In step S2, during spraying, the air inlet pressure of the spray gun is 2-3.5 bar, and the number of spraying times is 2-4 times.

6. The ceramic oxide hydrogen permeation barrier composite coating according to claim 1, characterized in that: The substrate is any one of a planar device, a metal wire tube and a special-shaped device.

7. The ceramic oxide hydrogen permeation barrier composite coating according to claim 1, characterized in that: Before spraying, the substrate sample is cut by electric spark cutting, the surface to be sprayed is roughened by sandpaper, and ultrasonic cleaning is performed in ethanol for 10-20 minutes, wherein during the roughening, 240# and 400# metallographic sandpapers are used in sequence for polishing.